A Frequent Toll‐Like Receptor 1 Gene Polymorphism Affects NK‐ and T‐cell IFN‐γ Production and is Associated with Helicobacter pylori‐induced Gastric Disease. Issue 1 (28th August 2012) - Yang, Chin‐An; Scheibenbogen, Carmen; Bauer, Sandra; Kleinle, Christoph; Wex, Thomas; Bornschein, Jan; Malfertheiner, Peter; Hellmig, Stephan; Schumann, Ralf R.; Hamann, Lutz
Abstract Background Helicobacter pylori infects approximately 50% of the world population. Among the infected individuals, only 10–20% develop peptic ulcers and <3% progress to gastric cancer (GC). Th1‐predominant immune responses have been suggested to underlie H. pylori‐induced gastric diseases. However, the reason for a strong inter‐individual variation of susceptibility and course of the disease is currently far from being understood. It has been shown that H. pylori stimulates the host's Toll‐like receptor (TLR) 2/1 complex. Furthermore, the single nucleotide polymorphism (SNP) I602S of TLR1 alters the inflammatory cytokine response of monocytes. Therefore, we hypothesized an association of this TLR1 SNP with H. pylori‐mediated gastric pathologies. Materials and Methods Subjects with different TLR1 genotypes were analyzed for their IFN‐γ response of NK‐ and T‐cells. We further genotyped 548 patients with gastric diseases for this SNP and compared patients with gastritis with those having ulcer, and patients with high‐risk gastritis versus patients with GC. Results Homozygous 602S allele carriers exhibited impaired in vitro IFN‐γ responses to the TLR2/1 agonist Pam3CSK4. The TLR1 I602S SNP is significantly associated with GC (p = .002) and gastric ulcer (p = .051). Odds ratios showed significantly reduced risk regarding GC and peptic ulcer for the homozygous mutated genotype. The odds ratios were 0.4 (95% CI, 0.22–0.72) and 0.588 (95% CI, 0.35–1.00), respectively. Conclusion In conclusion, our results suggest that the nonfunctional TLR1 602S/S genotype is associated with a reduced risk of H. pylori‐induced gastric diseases, probably via diminished Th1 responses.